2010
DOI: 10.1021/nn9015746
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Assembly of Biodegradable Plasmonic Nanoclusters for Near-Infrared Imaging and Therapeutic Applications

Abstract: Metal nanoparticles with surface plasmon resonance (SPR) in the near-infrared region (NIR) are of great interest for imaging and therapy. Presently, gold nanoparticles with NIR absorbance are typically larger than 50nm, above the threshold size of ~5 nm required for efficient renal clearance. As these nanoparticles are not biodegradable, concerns about long-term toxicity have restricted their translation into the clinic. Here, we address this problem by developing a flexible platform for the kinetically-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
191
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(203 citation statements)
references
References 39 publications
5
191
3
4
Order By: Relevance
“…It is known that both somatic and stem cells take up nanoparticles via early endosomes, are stored in late endosomes and lysosomes, and are eventually excreted from the cell. 31 In the current study, strong PA signals were detected from the ASC-cultured gels for more than 2 weeks. Even though the GNTs in ASC/gels (at 750 nm) showed significantly brighter PA signals on day 16, it was shown here that the degradation of PFGs, which occurred in the second week of the culture period, correlated with the increased PA signals due to the increased concentration of GNTs/volume of gel.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…It is known that both somatic and stem cells take up nanoparticles via early endosomes, are stored in late endosomes and lysosomes, and are eventually excreted from the cell. 31 In the current study, strong PA signals were detected from the ASC-cultured gels for more than 2 weeks. Even though the GNTs in ASC/gels (at 750 nm) showed significantly brighter PA signals on day 16, it was shown here that the degradation of PFGs, which occurred in the second week of the culture period, correlated with the increased PA signals due to the increased concentration of GNTs/volume of gel.…”
supporting
confidence: 49%
“…This is due to the aggregation-induced plasmon resonance coupling, a phenomenon which is well described in the literature. [31][32] In addition, GNTs in the cells showed higher UV-visible absorbance than cells without GNT treatment. The effects of GNTs on cellular behavior and function can be varied depending on the cell type and particle features such as size, shape, and surface characteristics.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Inorganic nanoparticles are difficult to biodegrade and induce long-term toxicity, which hinders their application in clinical practice. 9 Particles smaller than 5.5 nm can be rapidly and efficiently removed by the kidneys, 9,10 which allows them to be used safely in the clinic. Recently, Zhang et al 10 reported that the renal clearance rate of glutathione-protected Au NCs (2.1 nm) was maximum at 2 hours after injection, and only 6% of Au could be detected in mice at 28 days.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the polymers play a role in holding the colloidal particles together to form spherical aggregates. 38 In other studies, synthesis of kinetically controlled, near-IR active, gold-coated IO nanoclusters from a dispersion of IO NPs, were reported. 8,9 Overall, magnetic nanoclusters consisting of primary magnetic NPs assembled through various noncovalent interactions provide high magnetization and good colloidal stability.…”
Section: Introductionmentioning
confidence: 98%